FAKTOR PENDUKUNG PENCAPAIAN KEMAMPUAN GURU SD INP 12/79 BIRU 1 DALAM MENGGUNAKAN APLIKASI UNTUK MENENTUKAN TINGKAT KESUKARAN SOAL MELALUI PELATIHAN - Sudarto, Sudarto; Muh. Idris Jafar; Rukayah Rukayah; Sitti Jauhar; Muliadi Muliadi (Bajang Institute, 2025)
The Community Partnership Program (CPP) partners are the teachers at SD Inp. 12/79 Biru 1 Watampone, Bone Regency. Objective: To describe the factors that support the achievement of teachers' abilities in training to find the level of difficulty of questions using applications. Data collection techniques included observation and questionnaires. Results and conclusions: the factors are supporting the success of the training in using an application to determine the difficulty level of sums include: curiosity, trainer strategies, a familiar training environment, easy-to-understand teaching/demonstrations by the trainer, direct individual guidance from the trainer, responsiveness to participant difficulties or needs, participants' perceived need for the training materials, systematic presentation of the materials, participant enthusiasm for participating in the activities, and the support from relevant parties.